2022
DOI: 10.1088/1361-651x/ac9d54
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation nucleation mechanisms during nanoindentation of concentrated FeNiCr alloys: unveiling the effects of Cr through molecular simulations

Abstract: Fe-based alloys with high chromium and nickel concentrations are very attractive for efficient energy production in extreme operating conditions. We perform molecular dynamics (MD) simulations of nanoindentation on FCC FeNiCr multicomponent materials. Equiatomic FeNi, Fe55Ni19Cr26, and Fe74Ni8Cr18 are tested by using established interatomic potentials and similar conditions, for the elucidation of key dislocation nucleation mechanisms and interactions. Generally, we find that the presence of Cr in these alloys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The primary strengthening factors were related to sluggish dislocation diffusions, reduced defect sizes, and the nucleation of tetrahedral SFs [26]. Dominguez-Gutierrez et al performed MD simulations of nanoindentation on FeNi, Fe 55 Ni 19 Cr 26 , and Fe 74 Ni 8 Cr 18 [27]. They found that the presence of Cr in these alloys reduces the mobility of prismatic dislocation loops and increases their area, regardless of crystallographic orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The primary strengthening factors were related to sluggish dislocation diffusions, reduced defect sizes, and the nucleation of tetrahedral SFs [26]. Dominguez-Gutierrez et al performed MD simulations of nanoindentation on FeNi, Fe 55 Ni 19 Cr 26 , and Fe 74 Ni 8 Cr 18 [27]. They found that the presence of Cr in these alloys reduces the mobility of prismatic dislocation loops and increases their area, regardless of crystallographic orientation.…”
Section: Introductionmentioning
confidence: 99%